Measuring the Mechanical Effects of Egg Transport in Field and Modelled Conditions - Tímea Ágnes Torma; Katalin Kovácsné Gaal (Chemical Engineering Transactions)
Global food demand is expected to double by 2050, putting immense pressure on agro-food supply chains. As non-agricultural activities gain prominence within the food supply chain, a systemic approach is needed to address sustainability challenges. However, this is a learning process, because of the complexity of hatching egg transport, similar to a three-arm balance of transport condition, packaging material and egg quality. Changes made in the name of sustainability can sometimes cause unintended negative effects. Plastic trays are often favoured over paper ones for sustainability purposes in egg transport. However, they may contribute to higher egg breakage and reduced hatchability, increasing the carbon footprint due to the loss of day-old chicks. Since hatching eggs are more valuable than table eggs, any damage during transport results in greater economic loss. This study investigated the mechanical impact on eggs during 41 road transports, utilizing g-force acceleration loggers to collect data. A significant relationship was found between cargo weight, egg breakage, hatchability, embryo mortality, and g-force frequency. Seasonality also played a crucial role in hatchability, even when transport temperatures were within acceptable limits. Simulated trials using vibrating transport devices were conducted to better control mechanical impact. Eggs from one flock were used to minimize variables. Results showed a significant (P